Optimizing Health Communication: Public Engagement Analysis on TikTok by the Indonesian Ministry of Health - Ririn Wulansari; Handayani, Oktia Woro Kasmini; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
The increased use of social media in health promotion enables wider public outreach and engagement. This study aims to analyze factors affecting public engagement with TikTok content posted by the Indonesian Ministry of Health on the official account @kemenkesri. Using a quantitative content analysis of 184 videos from January 2023 to June 2024, data was collected through web scraping and analyzed using negative binomial regression. The independent variables examined included video duration, title length, video theme, type, and dialogue flow, while engagement was measured through likes, comments, and shares. The findings reveal that title length (p < 0.001), video theme (p = 0.004), type (p < 0.01), and dialogue flow (p < 0.05) positively influenced engagement, while video duration had a significant negative effect (p < 0.05). These results indicate that brief, visually engaging, and interactive content can significantly enhance audience interaction with health messages. This study provides recommendations for optimizing digital health communication strategies on social media to effectively convey health information to a broad audience.